2022
DOI: 10.30537/sjet.v5i1.982
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rice Residues as Potential Energy Source in Pakistan

Abstract: Pakistan produces enormous quantity of biomass wastes for example rice straw (RS) and rice husk (RH), wheat straw, and other biomass wastes that are being burned in the field after crop harvest to prepare the land for next crop. Biomass is known as potential energy source which can be effectively utilized as an alternative to fossil fuels. This study aims to assess the energy potential and gaseous pollutant emissions from rice residues such as RS and RH. The Energy potential of crop residues in Pakistan was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…From the results, it has been found that the metal concentration of biodiesel blended fuel B30 is lower than that of diesel fuel D100. This is due to the maximum lubricity present in biodiesel-blended fuel (Memon, 2022). The average percentage is Mn (17.89%), respectively.…”
Section: Manganese Wearsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results, it has been found that the metal concentration of biodiesel blended fuel B30 is lower than that of diesel fuel D100. This is due to the maximum lubricity present in biodiesel-blended fuel (Memon, 2022). The average percentage is Mn (17.89%), respectively.…”
Section: Manganese Wearsmentioning
confidence: 99%
“…On average, there is a notable reduction of 58.2% in the Fe wear concentration within the biodiesel blend. Several engine components, including the gearbox, piston rings, bearings, cylinder liners, and camshaft, contribute to the metal concentration in the lubricant oil (Memon, 2022).…”
Section: Iron Wearmentioning
confidence: 99%
“…Families use about 2300 Kg of firewood each year, 1200 Kg of crop waste, and 1500 Kg of manure. The author of [54] claims that the traditional way of resource use creates gases that are hazardous to human health, and this method is 25% less efficient. Along with other countries such as the United States, Germany, and Denmark, Pakistan's AEDB has examined the possibilities of bagasse and waste for electricity generation in Pakistan [55].…”
Section: Pakistan's Fossil Fuels and Renewable Energy Potential And R...mentioning
confidence: 99%
“…Pakistan has ability to produce barley is gradually declining because of inadequate soil fertility, degraded soil health, and environmental stressors. Pakistan produced 67,000 tonnes in 2014, but in 2019 and 2020 that number declined to 63,000 tonnes [ 3 , 4 ]. The World Food Organization (FAO) reported that almost 47 million hectares of land are under barley cultivation worldwide, with a mean annual production of 31,000 kg per hectare.…”
Section: Introductionmentioning
confidence: 99%